A polyol-stevia blended sugar replacer exhibits low glycemic response among human subjects. (October 2019) - Ng, Allan W.R.; Loh, K.K.; Gupta, Neeraj; Narayanan, Kumaran
Summary: Background & aims: Consumption of sugars in food and beverages has increased at an alarming rate. While excessive daily sugar intake has been well-associated as the onset of medical complications, additional sugars are still used in manufactured food products just to satisfy the consumers' needs. Hence, there is a need to develop sugar replacers that have low glycemic response without compromising the organoleptic characteristics of food products. This study aimed to determine if SUITENA™, a novel sweetener containing erythritol, xylitol, and Stevia, has low glycemic response upon consumption by human subjects. Methods: Six human subjects were randomly chosen and were healthy at the point of experimentation. Capillary blood was collected via finger-prick method to monitor the glycemic response of every individual for 90 min after ingestion of sugar solution. Results: It was found that the mean area under the curve (AUC) of the dextrose standard was 11.8-fold higher ( p < 0.05) than the AUC of SUITENA™. SUITENA™ was not able to increase blood glucose level for up to 90 min while a spike in blood glucose level was observed from 15 min post-consumption of dextrose solution. We found that SUITENA™ has elicited a glycemic response 8% relative to the standard. Such low glycemic response has been reported by studies on other novel sugars. Conclusion: This preliminary finding suggested that SUITENA™ is a healthier alternative to fast sugars due to its low glycemic response. A larger sampling size is required to confirm the results.